Enhancing English Language Learnings Communicative Production through Open Creative Tasks (2020)
ABSTRACT: This action research study explores a Task Based Learning unit about students’ production with 23 high school ELLs at a private school in Colombia. Actions included a unit design about travel diaries and creative tasks: matching, listing, brainstorming, guided and independent practice. Data included observations, students ‘work, interviews with students, and a teacher journal. The results revealed that students were more confident when being showed the process of formal production and communicating their own experiences rather than making up information or talking about someone else.